Teachers' Attitudes toward Using Activities while Teaching English to Young Learners - Sensoy, Seniz; Ozad, Bahire Efe (Ani Yayincilik, 2009)
Problem statement: Since the beginning of the new millennium, the English language has become the dominant international language. Consequently, the need to learn English has increased and teaching English to young learners has become a worldwide practice. The way children learn a second or foreign language differs from the adult approach toward learning. Children gain literacy in the traditional sense and have a shorter concentration span than adults. They are active and consider learning a kind of play. Recognition of these differences led to the proliferation of materials developed for young English learners. Accordingly, activities used when teaching English to young learners expanded in variety. In North Cyprus, teaching English as a foreign language begins as early as preschool. This has been in practice since 2005. However, there is a dearth of research into teachers' attitudes toward using different activities and which activities are favored most in teaching English to young learners in North Cyprus. Purpose of the study: This study explores the attitudes of teachers toward using different activities while teaching English to young learners in pre-school and years one and two in primary schools in North Cyprus in the 2006-2007 academic year. It also seeks to find out whether there are differences in the attitudes of preschool and primary school English teachers toward the variety of activities collected through observing teachers. Cluster sampling was used and 110 preschool and primary school English teachers participated in the study. Data was collected through an in-house questionnaire designed according to the five-point Likert scale. Findings and Results: Data suggests that both pre-school and primary school teachers are in favor of using different activities while teaching English to young learners. Teachers demonstrated a positive attitude toward using different activities. The results of the independent samples t-test suggest that there is no significant difference between the responses of pre-school and primary school teachers. The only significant difference is found in whether English should be taught through using language in games. A bivariate analysis indicated a very strong relationship between responses given to the use of different activities. Conclusions and Recommendations: Pre-school and primary school teachers teaching English in North Cyprus have a positive attitude toward using a variety of activities. The ages of these learners are close to each other and their development is similar. Therefore, the results of the study are parallel to this fact and teachers' attitudes toward different activities do show great similarities. In the future, if research is conducted on similar issues, it is recommended that gender, previous training, and length of experience of teachers should be taken into consideration.
Keywords: English for Young Learners (EYL); North Cyprus; primary school; preschool; activities